q-Wakimoto Modules and Integral Formulae of Solutions of the Quantum Knizhnik-Zamolodchikov Equations - Kuroki, K. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
Matrix elements of intertwining operators between q-Wakimoto modules associated to the tensor product of representations of Uq(^sl2) with arbitrary spins are studied. It is shown that they coincide with the Tarasov-Varchenko's formulae of the solutions of the qKZ equations. The result generalizes that of the previous paper [Kuroki K., Nakayashiki A., SIGMA 4 (2008), 049, 13 pages].